Designer clown fishes: Unraveling the ambiguities - Anikuttan, Kuttan Kuravamparambu; Rameshkumar, Palsamy; Nazar, Abdul Khudus; Jayakumar, Rengarajan; Tamilmani, Govindan; Sakthivel, Mohammed; Sankar, Murugesan; Bavithra, Rajendran; Johnson, Belevendran; Krishnaveni, Nataraj; Mercy, Augustin Angela; Moulitharan, Nallathambi; et al. (Frontiers in Marine Science, 2022)
The global marine ornamental fish trade is dominated by wild collected fishes and the contribution from hatchery production is less than 10 percentage of the total. Hatchery production is considered to be the only long term sustainable option to reduce the fishing pressure on wild population and also to safeguard the delicate coral reef ecosystem which houses most of the marine ornamental species. Among the hatchery produced fishes that are being traded, clown fishes form a dominant group and a recent addition to this list are the designer clown fishes, which are costlier than other clown fishes due to their rare and attractive colour patterns. However, ambiguities about designer clownfish such as its production (wild caught, captive bred, or genetically modified) and taxonomic identity still exists among the general public and hobbyists, as scientific reports on these aspects have not yet been published, even though few aquaculture companies display the photos of designer clown fishes in their websites. The common names for designer clown fishes (such as Platinum, Picasso, Snowflake etc) have been given by the aquaculture companies/traders solely based on the colour patterns or designs on the fish body. The paper describes in detail about the production of designer clown fish through captive breeding, followed by elucidating the taxonomic identity of two easily distinguishable designer clown fishes,viz;Picasso and Platinum. Both classical taxonomic tools as well as molecular methods were employed to elucidate the taxonomic identity. The morpho-merisitic characters of Picasso and Platinum were similar to that of Amphprion percula.The partial COI sequences of Picasso and Platinum clown fish were submitted to NCBI GenBank with the accession numbers MT947238 and MT947239 respectively which had maximum similarity to sequences of Amphiprion percula already deposited in NCBI, GenBank. The designer clown fishes exhibited protrandrous hermaphroditism with monogamous mating behavior. Egg incubation period ranged from 7-8days and the larval rearing was carried out with live feeds such as rotifers andArtemia under greenwater technique using microalgae, Nannochloropsis oculata. This paper can thus unravel the ambiguities related to production of designer clown fishes as well as its taxonomy